Apakah Kualitas Pelayanan, Kepuasan Nasabah dan Citra Perusahaan Berpengaruh Terhadap Loyalitas Nasabah ? - Muh. Shadri Kahar Muang; Jibria Ratna Yasir (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
This study proposes an idea to analyze how the role of Service Quality, Customer Satisfaction and Corporate Image in building Customer Loyalty at PT. Bank Central Asia KCU Makassar. This research uses the method quantitative with multiple linear analysis using 100 samples. The results of this study indicate that Service Quality variable (X1), Customer Satisfaction (X2), Company Image (X3) have a significant effect either partially or simultaneously on Customer Loyalty because it has a probability value of 0.000 0.05. While the coefficient of determination (Adjusted R Square) obtained is 0.937. This means that 93.7% of customer loyalty can be explained by the three dependent variables, while the remaining 6.3% of customer loyalty is influenced by other variables. This research contributes directly theoretically to the progress or development of understanding of the phenomenon of loyalty for the banking world in Indonesia and empirically able to make an active contribution to the banking and marketing team in managing loyalty and retaining customers. Further tracing and further research is needed by using a wider variety of research approaches, additions and changes to sampling techniques and adding other new variables. which is thought to also affect the formation of customer loyalty.